The Effects of Mucopolysaccharide Polysulphate on Hydration and Elasticity of Human Skin - Rungsima Wanitphakdeedecha; Sasima Eimpunth; Woraphong Manuskiatti (Hindawi Limited, 2011)
Background. Mucopolysaccharide polysulphate (MPS) has been used in medicine as an anti-inflammatory and antithrombotic agent for over 50 years. Its chemical structure permits considerable hydrogen bonding with adjacent water molecules, which effectively leads to hydration of the surrounding tissue. In addition, it stimulates endogenous hyaluronate synthesis, resulting in an increase in water-binding capacity and viscoelasticity of the skin. Objective. To study the efficacy of 0.1% MPS on hydration and elasticity of human skin. Methods. The first part of this study was a randomized double blind placebo-controlled study which included 60 female volunteers aged 30-45 years with dry skin, defined by Corneometer CM 825. The volunteers were treated with either 0.1% MPS or vehicle control. All subjects were asked to apply 1 g of cream to their face twice daily for a total period of 4 weeks. Skin hydration and elasticity were measured at baseline and week 4 with Corneometer CM 825 and cutometer MPA 580, respectively, at forehead and both cheeks. The second part of this study focused on the efficacy of 0.1% MPS on skin hydration after single application. 20 female volunteers aged 30-45 years with dry skin, defined by Corneometer CM 825, were recruited to the study. All subjects were asked to apply 2 g of 0.1% MPS cream on entirely randomly selected forearm. Skin hydration at the middle of both forearms was measured at baseline, immediately after application, and every 1 hour after application for a period of 10 hours. Results. 57 subjects (28 in vehicle control group, 29 in MPS) completed treatment protocol. The baseline skin hydration of both groups was not significantly different (P=0.47). Hower, there was a statistically significant difference in skin hydration at 4 weeks between MPS and placebo group (P=0.01). Skin elasticity was significantly improved at week 4 in both groups (vehicle-control, P<0.01, and MPS, P<0.01). However, no significant difference in skin elasticity between MPS and vehicle-control group was noted (P=0.15). Lastly, there was a statistically significant improvement in skin hydration after a single application (P<0.01). This improvement was maintained for 10 hours. Conclusions. MPS provided improvement of skin hydration but not skin elasticity in woman with dry skin, compared with vehicle control. And MPS improved the skin hydration for at least 10 hours after single application.